Cell and molecular signaling, and transport pathways involved in growth factor control of synaptic development and function - Nancy Y. Ip (Frontiers Research Topics, 2015)
Brain derived neurotophic factor (BDNF) and its receptor tropomyosin receptor kinase B (TrkB) signaling has been extensively studied for its roles in the central nervous system (CNS) ranging from cell survival, axonal and dendritic growth and synapse formation. Intracellular signaling pathways triggered by BDNF activate gene transcription, translation, post-translational functions, trafficking of key synaptic proteins, and synaptic release mechanism. BDNF-TrkB signaling mediates long-lasting activity-modulated synaptic changes on excitatory and inhibitory neurons and plays significant roles in circuit development and modulation. Furthermore, this pathway is critical for learning, memory, sensory processing and other cognitive functions, and is implicated in neurological and psychiatric diseases. In addition to BDNF, more recent studies have identified new "growth" factors that play important roles in the development, maturation and maintenance and modulation of synaptic function. However, details of the cytoplamic signaling systems downstream of these synaptogenic factors are often less understood than conventional neurotophin signaling. This e-Book has collected original studies and review articles that present cellular and molecular mechanisms concerning activity-dependent synapse formation and their implications for behavior and brain disorders. It is our hope that readers will perceive this volume as a showcase for diversity and complexity of synaptogenic growth factors, and will stimulate further studies in this field.